Psychometric properties of the Lithuanian version of the Hierarchical Personality Inventory for Children (HiPIC) - Grauslienė, I.; Barkauskienė, R. (Psichologija, 2013)
The Five-factor Model (FFM) is currently the most common dimensional approach to personality traits. Research of children’s personality traits is a new challenge for scientists, which motivates to step into an almost unknown area. These investigations were encouraged by the success of the Five-factor Model research on adults: scientists quite intensively started going deeper into the research of children’s personality traits starting from early childhood till late adolescence. The present study was designed to investigate the psychometric properties of the Lithuanian version of the Hierarchical Personality Inventory for Children (HiPIC, Mervielde and De Fruyt, 1999). The HiPIC is an instrument to assess the five dimensions of the five-factor model for children between 6 and 12 years. The HiPIC measures 18 facets grouped into five dimensions: Extraversion, Conscientiousness, Benevolence, Emotional Stability, and Imagination (Mervielde and De Fruyt, 1999). This inventory, contrary to the NEO PI-R, was developed using a bottom-up strategy (Mervielde and De Fruyt, 2002). The present research included three phases. A parent rating was obtained for 739 children all aged between 7 and 11. Some children were rated by their both parents, some by mother or farther; 1081 parents filled the questionnaires. The HiPIC was distributed in the classroom by the researchers to the children who had to bring the questionnaire to their parents. All 144 HiPIC items were translated and retranslated into Lithuanian by professional translators with the author of the inventory supervision during all three phases of the research.The facets’ internal consistency was estimated by the Cronbach alpha coefficient. At the domain level, the internal consistency ranged from 0.808 to 0.909, and at the facet level the internal consistency ranged within 0.574–0.873. In order to assess the construct validity, we conducted a principal componentexploratory factor analysis with the varimax rotation of the 18 facet scales. In order to compare the factorial structure with the theoretical structure of the inventory, first we chose to extract five factors, but the further factor analysis showed that the Lithuanian HiPIC version had more arguments for a four-factor structure with a blend of the Conscientiousness and Imagination domains and explaining 71.93% of variance. The Lithuanian version of the HiPIC is reliable, although construct validity indicators had some weaknesses. The internal consistencies are satisfactory and similar to those found with the original Flemish version and the French version. To conclude, the Lithuanian HiPIC version can be used in scientific research in assessing children’s personality traits. This research was funded by a grant (No. MIP-016/2012) from the Research Council of Lithuania.
Keywords: children’s personality traits; Five Factor Model; HiPIC; psychometric properties